Evaluation of customer oriented success factors in mobile commerce using fuzzy AHP - Golam Kabir; M. Ahsan Akhtar Hasin (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: With the development of information technology, ordinary commercial activities are evolving into e-commerce. In e-commerce, users can access services from any place as long as information technology is available. Currently, e-commerce is moving toward mobile commerce that allows users to do commercial activities while they are moving. This study aims to elucidate the factors that affect success in mobile commerce, and then evaluate and rate these factors by analyzing components of commercial activity in the mobile internet environment and give an evaluation method for mobile commerce in order to help researches and managers to determine the drawbacks and opportunities. Design/methodology/approach: A consumer survey was conducted through a structured undisguised questionnaire towards meeting the objectives of the study. An online questionnaire constituted the data collection instrument, while only internet users participated in the sample. The main goal of the questionnaire is to identify the success factors or criteria and sub-criteria for mobile commerce from the viewpoint of users' perception and to assess the decision-making executives for pair-wise comparisons using the fuzzy analytic hierarchical process (FAHP). Findings: A subjective and objective integrated approach has been put forward to determine attributes weights in Fuzzy AHP problems. The study identified the success factors or criteria and sub-criteria for mobile commerce from the viewpoint of users' perception. The main attractive factors for the customer are the trust and mobility factors. In addition, content quality, system quality, use, support, personalization factors are also important.Research limitations/implications: Sampling is a major limitation in this study. Since the survey was conducted based on a sample in Bangladesh, the prudent reader may need to interpret the results of the study with caution, particularly with respect to the generalization of research findings to Bangladesh mobile commerce customers as a whole. Practical implications: The principal practical implication is to identify the success factors or criteria and sub-criteria for mobile commerce from the viewpoint of users' perception. The criteria and decision alternatives or sub-criteria that are applied in this evaluation were selected based on the feedback from the questionnaire and literature review. On the other hand, from a professional point of view, future research should make several extensions to measure users' satisfaction with mobile commerce using user satisfaction index and evaluate commercial activities in ubiquitous environment, which is a process in the transition of commerce, using the success factors and alternatives of mobile commerce. Originality/value: There are no comparative studies about evaluation of customer oriented success factors for Bangladeshi mobile commerce users. A structured analysis of such customer-oriented factors provides good insights, and will help business managers to time the launch of mobile commerce businesses. It will become a useful assessment model for predicting and evaluating market tendencies.
Keywords: 650; fuzzy AHP; MCDM; mobile commerce; success factors